Hyperhaemolytic transfusion reaction in two β‐thalassaemia major patients: The role of eculizumab. (16th August 2021) - Pantelidou, Despoina; Pilalas, Dimitrios; Daios, Stylianos; Polychronopoulos, George; Papadopoulou, Despoina; Perifanis, Vassilios; Savopoulos, Christos; Kaiafa, Georgia
Abstract: What is known and objective: Hyperhaemolytic transfusion reactions are rare life‐threatening events predominantly affecting patients with haemoglobinopathies. We report two cases in β‐thalassaemia major patients on chronic transfusion therapy and highlight the role of eculizumab in its management. Case summary: Patient 1 presented with intravascular haemolysis on day 7 (D7) post‐transfusion and responded to treatment with corticosteroids and intravenous immunoglobulin. However, patient 2 presented with severe symptomatic anaemia (D4 post‐transfusion) unresponsive to the aforementioned measures. Eculizumab administration led to resolution of the hyperhaemolysis. What is new and conclusion: We report the successful management of hyperhaemolysis with eculizumab in a β‐thalassemia major patient. Abstract : We report the successful treatment of hyperhaemolytic transfusion reaction, a life‐threatening complication of RBC transfusion, with eculizumab in a patient with β‐thalassaemia major.